Exercise: Just what the doctor ordered, but why? Elucidating mechanisms for women's increased HDL benefit from exercise. (31st December 2021) - Bernier, Rachel A.; Banks, Sarah J.; Clark, Alexandra L.; Shepherd, Alyx L.; Sundermann, Erin E.
Abstract: Background: High‐density lipoprotein (HDL) is protective against cardiovascular disease (Di Angelantonio et al., 2009), a risk factor for AD pathogenesis (Brickman et al., 2015). Aerobic exercise can increase HDL concentration (Hsu et al., 2019), and evidence suggests this HDL benefit occurs more so in women than in men (Werner et al., 1995). Both HDL and exercise are associated with tumor necrosis factor alpha (TNFα), a proinflammatory cytokine (Park et al., 2003). Given known sex differences in the immune response (Hanamsagar & Bilbo, 2016), TNFα levels may represent a potential mechanism by which women's HDL levels benefit more so from exercise. We sought to replicate the stronger exercise‐HDL link in women versus men and examine TNFα as a potential mediator in a group of cognitively normal (CN) older adults. Method: This study included 2957 CN participants (51% women; 41% Black, 59% White; mean age=73.6 (SD=2.9) years) from the Health, Aging, and Body Composition (Health ABC) study who underwent a blood draw for biomarker analysis of HDL and TNFα levels. Exercise level was measured via a standardized physical activity questionnaire categorized (0‐6) based on Kcal/week for all types of walking, exercise, and recreation, and examined continuously. Regression analyses were employed to examine exercise‐by‐sex interactions on HDL‐level (mg/dL) and the mediating effect of TNFα (pg/mL). Covariates included age, race, and body mass index. Result: Regressions adjusting for covariates revealed significant exercise‐by‐sex interactions on HDL (ß=0.12, p=.022), whereby higher levels of exercise related to higher HDL in women (ß=0.06, p=.023) but not in men (ß=‐0.01, p=.653). TNFα level negatively related to HDL in women (ß=‐0.24, p<.001), and adjusting for TNFα eliminated the female‐specific exercise‐HDL association (ß=0.04, p=.150). Conclusion: This female‐specific association was eliminated when adjusting for TNFα, suggesting that exercise may benefit HDL in women through ameliorating effects on the neuroinflammatory pathway. Findings underscore the importance of exercise as a mitigator of vascular risk and, in turn, AD risk, particularly in women. Future studies should examine these interrelationships longitudinally and across the AD spectrum.